Significance of Chapels in Forming the Regional Tradition of Serbian Medieval Architecture - Maltseva, Svetlana V. (Actual Problems of Theory and History of Art, 2025)
The paper analyses the development of some peculiar elements determining the national specific of Serbian church architecture — the chapels dedicated to the local cults. These chapels emerge in Serbian churches in the early 13th c., when the national architectural tradition begins to form. During the whole period of existence of this tradition these chapels where placed in specific places of the church and influenced its architectural typology, its spatial composition and the programme of monumental decoration.
Keywords: Medieval Serbian architecture; chapels; architectural typology; spatial composition of the church